Normal gastric tissue Helicobacter pylori infection is associated with epigenetic age acceleration, increased mitotic tick rate, tissue cell composition, and Natural Killer cell methylation alterations - Vlasac, Irma M; Christensen, Brock C; Salas, Lucas A (bioRxiv, 2023)
Gastric adenocarcinomas are a leading cause of global mortality, associated with chronic infection with . The mechanisms by which infection with contributes to carcinogenesis are not well understood. Recent studies from subjects with and without gastric cancer have identified significant DNA methylation alterations in normal gastric mucosa associated with infection and gastric cancer risk. Here we further investigated DNA methylation alterations in normal gastric mucosa in gastric cancer cases (n = 42) and control subjects (n = 42) with infection data. We assessed tissue cell type composition, DNA methylation alterations within cell populations, epigenetic aging, and repetitive element methylation. In normal gastric mucosa of both gastric cancer cases and control subjects, we observed increased epigenetic age acceleration associated with infection. We also observed an increased mitotic tick rate associated with infection in both gastric cancer cases and controls. Significant differences in immune cell populations associated with infection in normal tissue from cancer cases and controls were identified using DNA methylation cell type deconvolution. We also found natural killer cell-specific methylation alterations in normal mucosa from gastric cancer patients with infection. Our findings from normal gastric mucosa provide insight into underlying cellular composition and epigenetic aspects of associated gastric cancer etiology.